Determination of appropriate exposure to fluoride in non-EME countries in the future Determinação da exposição apropriada a fluoreto no futuro para países de economia de mercado não estabilizada - Jaime Aparecido Cury; Cínthia Pereira Machado Tabchoury (University of São Paulo, 2003)
An appropriate exposure to fluoride must be able to interfere with the development of dental caries (benefit) without great concern for dental fluorosis (risks). This condition in relation to individual seems feasible leading to a rational use of fluoride. Nevertheless, dealing with population and particularly non-EME countries (non-Established Market Economies or developing), the most suitable method of fluoride use will depend on each nation. On the other hand, each country should have a public health program to control dental caries as part of its health system. The choice between fluoridated dentifrice or fluoridated drinking water and the option for salt will depend on its applicability in each country. At the same time, it is important that either the appropriate exposure to a community method of fluoride use as well as the association with other methods and preventive measures in relation to risks-benefits are evaluated for each country. The determination of an appropriate exposure to fluoride in non-EME countries in the future will depend on critical analysis of how it has been used at present. Available data have shown that some non-EME countries have even been able to revert the dramatic situation of dental caries in their population, but in others caries experience continues a public health problem. Nevertheless, in other countries the increase in caries prevalence, which was expected, has not occurred but endemic fluorosis has been a concern. The challenges for non-EME countries are huge and identical solutions cannot be used for distinct problems. Uma exposição apropriada ao fluoreto é aquela capaz de interferir com o desenvolvimento de cárie dental (benefício) sem grandes preocupações com fluorose dental (riscos). Esta condição em termos de indivíduo parece factível levando ao uso racional do fluoreto. Entrentanto, em se tratando de população e particularmente países non-EME, o método mais adequado de usar fluoreto vai depender de cada nação. Por outro lado, é imprescindível que haja uma política nacional de um método coletivo para controlar cárie como integrante do sistema de saúde de cada país. A escolha entre dentifrício fluoretado ou água fluoretada e a opção por sal vai depender da sua aplicabilidade a cada país. Ao mesmo tempo, é importante que para cada país seja avaliada não só a exposição apropriada do método coletivo de usar fluoreto, assim como a associação com outros métodos e meios em termos de riscos-benefícios. A determinação da exposição apropriada a fluoreto nos países non-EME no futuro dependerá da análise crítica de como ele tem sido usado no presente. Dados disponíveis têm mostrado que alguns países non-EME têm inclusive conseguido reverter a situação dramática de cárie de sua população, mas em outros a experiência de cárie continua dramática. Entretanto, em outros países não tem ocorrido um aumento da prevalência de cárie que se esperaria, mas fluorose endêmica é uma preocupação. Os desafios para países non-EME são imensos e para problemas distintos não existem as mesmas soluções.